Eco-Terrorism: assessing current threats and trends - Silke, Andrew (Pool Reinsurance (PoolRe), 2022)
Eco-terrorism is motivated by a diverse range of issues and is mainly carried out by lone actors or relatively small and diffuse groupings. Attacks primarily target the destruction of property and vandalism, and are 70 times less likely to result in fatalities compared to the average terrorist attack recorded in the Global Terrorism Database. The most commonly used weapons are incendiary and explosive devices. While only used in a small number of cases, environmentally-motivated terrorist attacks are, however, more likely to involve chemical, biological or radiological weapons compared to average terrorist attacks. Businesses are the primary targets for environmentally-motivated terrorism, followed by research/educational facilities and personnel. Trends currently do not show a rise in traditional environmentally-motivated terrorist attacks connected to the climate change crisis. This may change, however, as the climate crisis worsens and may also be affected if plans to more heavily criminalise non-violent climate protest activity are realised. The recent rise of eco-fascism indicates that environmentally-motivated narratives can be co-opted by other extremist ideologies and that this can have an impact on real-world violence. The potential for this to also eventually happen with regard to Islamist and nationalist-separatist extremism, for example, seems real, particularly in the context of a deepening climate crisis.